CALL (computer assisted language learning) wiki - Papadima-Sophocleous, Salomi (My University, 2012)
This paper discusses the importance of the use of new technologies as part of the pedagogy of language teacher training courses. It examines how wikis were used in a computer assisted language learning (CALL) course, which constituted a fourth-year compulsory component of a Bachelor of Arts in English Language and Literature course. The method of examination used is presented and the data is discussed to establish students’ perceptions of the usefulness of the use of new technologies in their learning, and more specifically the contribution of wiki in their CALL teacher training.
Keywords: Computer assisted language learning; Wiki; Teacher training